Vegetation development and soil conditions in reclaimed areas of former silica mines in Indonesia - Yunanto, Tedi; Wildan, Dadan; Suparno; Megawati; Santoso, Natasya (Brawijaya University, 2025)
To restore the function of ex-mining land according to its designation, the ex-mining area must be reclaimed. Ecological dynamics, especially soil conditions and the composition, structure, and biodiversity that occur in reclamation areas, need to be understood so that the reclamation area meets the criteria for the success of mine reclamation. This study aimed to understand the composition, structure, biodiversity, and soil conditions that influence growth in the reclamation area. The research was conducted in a silica mine reclamation area with a 17.8 m radius (r) circular plot (0.1 ha) of 10 plots (±1 ha) for vegetation and 9 points for soil sampling at a depth of 0-30 cm and 30-60 cm. In general, the results of the vegetation inventory show that the tree species recorded are dominated by Pinus merkusii, Hevea brasiliensis, and Enterolobium cyclocarpum with mean values of diameter, height, and low diversity conditions. The condition of soil physical and chemical properties in the reclamation area at both depths shows low mean values, which can affect the growth rate of plants in the reclamation area. The species of Schima wallichii that grow naturally in the reclamation area was found, indicating that the reclamation activities have created a good environment for other tree species to grow naturally. However, enrichment activities need to be carried out to increase biodiversity.